Ethics within a Spiritual/ Metaphysical World View towards Integral Value-based Education European Educationists: Steiner and Montessori - Ferrer, Albert (JOURNAL OF INDIAN EDUCATION, 2018)
Among the Western pioneers of integral value-based education, two authors deserve special attention in Europe: Steiner and Montessori. This paper outlines a common underlying background in both of them—Philosophical Idealism and Theosophy. According to the author, it is this special idealistic sensitiveness that compels the two renowned educationists to react against the technocratic and utilitarian mainstream school system and suggest new avenues for the pedagogic practice in a holistic, humanistic and even spiritual horizon which overcomes the valueless soulless patterns of modernity. If mainstream schooling is based upon a certain world view, which is materialistic and mechanistic, Steiner and Montessori’s pedagogic innovation is based upon another world view, which is humanistic and spiritual. In spite of different paths in professional terms and different personal contexts, they both put forward the same fundamental pedagogic principles deriving from this common underlying paradigm. From this point of view, the needed caution from mainstream schooling while approaching their philosophy of education should not overlook the contribution that they have made and they still can make to transform the educational system for better.